Physical Conditions Analysis of Professional Women Football Player in Malang City - Amiq, Fahrial; Angga, Prayogi Dwina; Saputro, Yulianto Dwi (Physical Education, Health and Recreation Study Program, Universitas Insan Budi Utomo, Indonesia, 2024)
This study aims to analyze physical performance, which is one of the dominant factors that will affect elite football athletes in Malang city, namely endurance, speed, agility, strength, and flexibility. This research includes research that is carried out systematically by raising existing data in the field. Meanwhile, the object of this study is the level of physical fitness of professional female footballers who are members of the Arema FC club, totaling 23 people. The tests that will be used to see the physical fitness of Arema Women FC athletes consist of (1) the Yo-Yo Test to measure endurance, (2) Arrowhead Agility to measure agility, and (3) Speed 30 meters to measure speed. (4) Standing Long Jump Test to measure explosive power; (5) Hip and Trunk Flexibility Test to measure flexibility Based on the results of the study after analyzing research data regarding the physical fitness level of the Arema Women FC football players, it can be inferred that they are in the medium category based on the aggregate results of all test components, which include endurance, agility, speed, explosive power, and flexibility.